Optimalisasi Pemasaran Digital dan Keterampilan Kreatif bagi UMKM Toko Buket bunga untuk Meningkatkan Kualitas dan Penjualan - Cahyani, Dwi; Firmansyah, Dio Dwi; Oktaviani, Dona; Sesilia, Dita Ayunda; Pratama, Reza Hardian (Welfare : Jurnal Pengabdian Masyarakat, 2024)
MSMEs (Micro, Small and Medium Enterprises) have an important role in the Indonesian economy, but often experience difficulties in developing digital marketing and improving creative skills. This community service program aims to optimize digital marketing and creative skills for flower bouquet shop MSMEs in order to increase product quality and sales volume. This activity is carried out through training, mentoring and direct practice related to digital marketing and product design innovation. The results show that participants were able to improve their skills in using digital platforms and create more creative products according to market trends. This program has a positive impact in increasing the competitiveness of MSMEs in the digital era.